2006
DOI: 10.1002/ajim.20338
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychosocial job stress on non‐fatal occupational injuries in small and medium‐sized manufacturing enterprises

Abstract: These data point to an independent relationship between psychosocial job stress and self-reported occupational injury in SMEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 39 publications
6
78
0
1
Order By: Relevance
“…In contrast, men showed no difference in occupa- tional injury rate according to decision latitude. In hospital workers, the risk for occupational injury was higher in workers with lower job control [Salminen et al, 2003], and female Japanese workers in small-and medium-sized manufacturing enterprises reported a significantly lower job control score than men, which was related to an observable increase in occupational injuries [Nakata et al, 2006]. In some studies, however, no correlation was observed between decision latitude and occupational injury [Murata et al, 2000;Swaen et al, 2004].…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, men showed no difference in occupa- tional injury rate according to decision latitude. In hospital workers, the risk for occupational injury was higher in workers with lower job control [Salminen et al, 2003], and female Japanese workers in small-and medium-sized manufacturing enterprises reported a significantly lower job control score than men, which was related to an observable increase in occupational injuries [Nakata et al, 2006]. In some studies, however, no correlation was observed between decision latitude and occupational injury [Murata et al, 2000;Swaen et al, 2004].…”
Section: Discussionmentioning
confidence: 94%
“…Fourth, it is possible that work-related stressors are an intermediated step in a pathway leading from depressive symptoms to the occurrence of occupational injuries. Several studies have demonstrated a relationship between occupational injury and work related stressors [e.g., decision latitude and job demand (Nakata et al 2006;Salminen et al 2003;Swaen et al 2004), low social support (Murata et al 2000;Wilkins and Beaudet 1998), interpersonal conXicts (Greiner et al 1998;Salminen et al 2003), job dissatisfaction (Dembe et al 2004;Holcom et al 1993;Li et al 2001;Nakata et al 2006)]. Conversely, these factors may aVect depressive symptoms, which in turn may work as intervening variables aVecting the occurrence of occupational injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a relationship between depressive symptoms and occupational injury (Cooper and Sutherland 1987;Nakata et al 2006;Peele and Tollerud 2005). The potential mechanisms of how depression plays a role in occupational injury remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The data was collected in a cross-sectional study with a self-rating questionnaire from August to December 2002 30,31) . The subjects were workers in SME manufacturing factories with 1 to 158 workers in Yashio city, Saitama prefecture, Japan.…”
Section: Subjectsmentioning
confidence: 99%